Respuesta :
Answer:
[tex]S{__{20}} = 197.5[/tex]
Step-by-step explanation:
The equation for A.P. is [tex]a{__n} = a{__1}+(n-1)d[/tex]
where An is the value of the nth sequence,
A1 is the value of the first sequence,
n is the number of sequence,
and d is the difference between each term in the A.P.
Given:
[tex]a{__1} + 2d = 8[/tex]
[tex]a{__1} + 6d = 9[/tex]
We can solve two unknowns with simulataneous equations.
[tex]a{__1} = a = \frac{15}{2}[/tex], [tex]d = \frac{1}{4}[/tex]
Now use the equation for sum of A.P., that is [tex]S{__n} = \frac{n}{2}(2a+(n-1)d)[/tex].
Plug in all the values.
[tex]S{__{20}} = \frac{20}{2}(2*(\frac{15}{2}) +(20-1)(\frac{1}{4} ))[/tex]
[tex]S{__{20}} = 197.5[/tex]
Answer:
Given That:-
- 3rd term of A.P. is 8.
- 7th term is 9 more than it's 4th term.
[tex] \: [/tex]
We have:
[tex] \dashrightarrow{ \green{ \rm{a_3 = 8}}}[/tex]
[tex]{ \dashrightarrow{ \green{ \rm {\: a_7 = a_4 + 9}}}}[/tex]
To Find:
- Sum of 20 term of an A.P.
[tex] \: [/tex]
So, we know:
- a + 2d = 8 ...(1)
- a + 6d = a + 3d + 9 ...(2)
[tex] \: [/tex]
[tex] \star \: { \boxed{ \pink{ \rm { a_3 = 8}}}} \: \star[/tex]
[tex]{ \large{ \dashrightarrow{{ \rm{a \: + \: 6d \: = \: a \: + \: 3d \: + \: 9 \: }}}}}[/tex]
[tex] \: [/tex]
[tex]{ \large{ \dashrightarrow{ \red{ \rm{a \: + \: 6d \: = \: a \: + \: 3d \: + \: 9}}}}}[/tex]
[tex]{ \large{ \dashrightarrow{ \red{ \rm{6d \: - 3d \: = \: 9}}}}}[/tex]
[tex]{ \large{ \dashrightarrow{ \red{ \rm{3d \: = \: 9}}}}}[/tex]
[tex]{ \large{ \dashrightarrow{ \red{ \rm{d \: = \: \frac{9}{3} }}}}}[/tex]
[tex]{ \large{ \dashrightarrow{ \red{ \rm{d \: = \: { \green{ \boxed{ \rm{3}}}}}}}}}[/tex]
So, putting the value of 'd' in Equation (1), we get:
[tex]{ \large{ \longrightarrow{ \rm{a \: + \: 2(3) \: = \: 8}}}}[/tex]
[tex]{ \large{ \longrightarrow{ \rm{a \: + \: 6 \: = \: 8}}}}[/tex]
[tex]{ \large{ \longrightarrow{ \rm{a \: = \: 8 \: - \: 6}}}}[/tex]
[tex]{ \large{ \longrightarrow{ \rm{ a\: = \:{ \green {\boxed{ 2}}}}}}}[/tex]
Now, Sum of 20th term of A.P. is :
[tex]{ \large{ \boxed{ \blue{ \rm{S_n \: = a + \frac{n}{2} \left[2a + (n - 1)d \right]}}}}}[/tex]
So, Putting:
- a = 2
- d = 3
- n = 20
[tex]{ \longrightarrow{ \rm{\large{S_n} \: = \: a \: + \frac{n}{2} \left[ 2a \: + (n - 1)d\right]}}}[/tex]
[tex]{ \longrightarrow{ \rm{ \large{S_n \: = \: 2 + \frac{20}{2} \left[ \: 2(2) + (20 - 1)(3) \: \right]}}}}[/tex]
[tex]{ \longrightarrow{ \rm{ \large{ S_n \: = \: 2 + 10\left[ 4 + (19)(3)\right]}}}}[/tex]
[tex]{ \longrightarrow{ \rm{ \large{S_n \: = \: 2 + 10\left[4 + 57 \right]}}}}[/tex]
[tex]{ \longrightarrow{ \rm{ \large{S_n \: = \: 2 + 10 \: \left[ \: 61 \: \right]}}}}[/tex]
[tex]{ \longrightarrow{ \rm{ \large{S_n \: = \: 2 + 610}}}}[/tex]
[tex]{ \longrightarrow{ \large{ \rm{S_n \: = \: { \green{ \boxed{612}}}}}}}[/tex]
Hence,
[tex]{ \boxed{ \pink{ \rm{Sum \: of \: 20 ^{th} \: term \: = \: 612 \: }}}}[/tex]